Global Supply Chain International Trade as Emerging Power: Case Study of PT. Toyota Motor Manufacturing towards the Decline of Exports in Southeast Asia in 2020 - Zettha Adietya Putri; Khoirunnisa Khoirunnisa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to explain how the global supply chain impacts international trade: a case study of pt. Toyota Motor Manufacturing on the decline in Indonesia's exports in Southeast Asia in 2020 and how the influence of work from home policies and reduction of human resources on export performance at PT. Toyota motor manufacturing. Which affects the global economic crisis and social impact due to the Covid-19 virus pandemic. The method in this study contains a process of comparing data by analyzing the literature of previous scientific studies and using qualitative research methods. The research compiled by the author is a descriptive literature study. Within the theoretical framework used in constructivism theory where this theory has learning that develops logical and analytical abilities, this paper is based on the experience of PT. Toyota Motor Manufacturing Indonesia (TMMIN) implemented the concept of a Work From Home policy on most of its employees in the aftermath of COVID-19 and stopped production for 2 weeks in April 2020.